Effects of informal institutions on the relationship between accounting measures of risk and bank distress - KANAGARETNAM, Kiridaran (Institutional Knowledge at Singapore Management University, 2017)
We investigate the effects of informal institutions (trust, religiosity and the media) on the relationship between accounting-based risk measures and bank distress. We conduct our analysis in two stages. In the first stage, we extend the prior literature by documenting a link between accounting-based risk measures and bank distress during the 2008-2009 financial crisis. In particular, given the environment characterized by rapid growth in financial innovation and complex financial transactions prior to the crisis, simple accounting-based risk measures continue to predict bank distress during this crisis period. In the second stage, we address our main research question related to the effects of selected informal institutions (societal trust, religiosity, and the media) in enhancing the predictive ability of accounting-based risk measures. As hypothesized, we find that these informal institutions enhance the predictive ability of accounting-based risk measures. Our results inform regulators that the focus on strengthening formal institutions should not ignore country-specific informal institutional structures.